Efficacy and plant growth promoting activity of novel strains of Bacillus spp. to control collar rot of chickpea (Cicer arietinum) in India - SONAL KUMAR; R K S TIWARI; V K NIRMALKAR; JAYANT SAHU (The Indian Journal of Agricultural Sciences)
The present study was carried out during 2022 and 2023 at Agriculture College and Research Station, Bilaspur, Chhattisgarh, focused on exploring native rhizospheric bacteria for managing soil-borne pathogen affecting chickpea (Cicer arietinum L.). Collar rot, caused by Sclerotium rolfsii, is a major threat to chickpea production. The study evaluated 104 native rhizospheric bacterial isolates collected from various agro climatic zones in Chhattisgarh for their efficacy against S. rolfsii in vitro. Among these isolates, 18 exhibited significant inhibition of S. rolfsii mycelial growth. Notably, certain isolates demonstrated remarkable effectiveness, with Bacillus subtilis (BI 28), B. tequilensis (BI 22), Bacillus subtilis (BI 68), Bacillus velezensis (BI 43), Bacillus subtilis (BI 49), and B. tequilensis (BI 31) showing the highest inhibition percentages ranging from 80.37–85.56%. Further analysis of chickpea growth parameters revealed that most isolates positively influenced root and shoot biomass, as well as root and shoot length, compared to the untreated control. Moreover, in vivo experiments demonstrated that all isolates enhanced seedling emergence and reduced post-emergence mortality rates compared to the control group. The findings suggested that these isolates hold potential for integrated management practices against collar rot in chickpea cultivation.